Visually significant ocular decompression retinopathy following laser peripheral iridotomy in a patient with primary acute angle-closure glaucoma - Sinan Ersan; Charles Zhang; Sandra F. Sieminski (American Journal of Ophthalmology Case Reports)
Purpose: We report a single case of ocular decompression retinopathy (ODR) following neodymium-doped yttrium aluminum garnet laser peripheral iridotomy (Nd:YAG LPI) for primary acute angle-closure glaucoma associated with delayed visual recovery secondary to optic nerve head edema and macular thickening. Observations: A 56-year-old female patient presented to the emergency department with primary acute angle-closure glaucoma. After topical and IV therapy did not improve intraocular pressure (IOP), an Nd:YAG LPI was performed. Upon follow up in the clinic, the patient continued to have poor visual acuity despite a normal IOP and clear cornea. Her exam revealed optic nerve head edema and macular thickening with scattered intraretinal hemorrhages in the peripheral retina, mimicking a vein occlusion but also consistent with ODR. Uncomplicated cataract surgery was performed due to a persistently closed angle and increasing IOP, but vision remained poor post-operatively. At post-operative month 1, optic nerve head edema and macular thickening ultimately resolved with an associated improvement of visual acuity. Conclusions: We report on a patient who developed visually significant ODR following Nd:YAG LPI. Recognizing this condition and distinguishing it from similar conditions, including central retinal vein occlusion, is crucial to avoid unnecessary treatment. Ancillary imaging including fluorescein angiography and ocular coherence tomography is helpful in confirming the diagnosis.